Fiscal policy reforms in India – Overviews - Palanichamy, A.P. (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Fiscal policy is the important instrument of Economic Development. A comprehensive tax policy to ensure speedy economic development must promote savings, encourage investments, provide a healthy economic climate and stable economic framework assures equitable distributing of gains of employment and reduces concentration of economic power. Appropriate measures have been taken by the Government of India to design its tax policy on the above lines. Tax concessions, relief and incentives have been provided to encourage saving and investment, fiscal incentives are being given for export promotion, excise duties are being rationalized, non-development expenditure is being kept in check. All these measures were yields some sources. But still there are many drawbacks with the tax system which are being carefully looked into.